Impact and Performance of Public Accounts Committees in the Niger Delta States: A Study of Delta, Ondo, and Abia States House of Assembly - Ojaduvba Jame Augoye (Journal of Social Science and Humanities, 2026)
This study conducted an empirical analysis of the impact and performance of public account committees in the Niger Delta States with emphasis on Delta, Edo and Abia States House of Assembly. The study aimed to achieve five objectives: (1) to understand how the PAC promotes accountability in public sector organizations, (2) to examine the relationship between the PAC and the Auditor-General in promoting accountability of public funds, (3) to assess the role of the PAC, civil society organizations (CSOs), and the PAC Tribunal in the South-South states of Nigeria in influencing the accountability of public funds in Ministries, Departments, and Agencies (MDAs) and other public institutions, (4) to identify the challenges faced by the PAC in promoting accountability, and (5) to analyze the impact of the PAC's directives and recommendations on public fund accountability. The research was conducted across the South-South states of Nigeria, using both descriptive and survey research designs. The data collected were analyzed using multiple regression. The findings of the study indicated that the quality of the PAC has a significant effect on the accountability of public funds in these states. Additionally, the timeliness of the PAC’s activities also significantly influences public fund accountability. On the other hand, political influence was found to have no significant effect on the accountability of public funds. Lastly, the PAC’s recommendations and appeals were shown to significantly affect the accountability of public funds in the region. The study concludes that the PAC has positively influenced the accountability of public funds, particularly through moderate follow-up of audit reports, timely discussions, and responses to audit recommendations. Despite these achievements, the study recommends that PAC members be trained in information technology to enhance their effectiveness and efficiency. Furthermore, it stresses the importance of ensuring full effectiveness of the PAC in promoting accountability by covering all aspects of expenditure and revenue auditing.